An Influence Analysis Of Product Quality, Brand Image, And Price On The Decision To Buy Toshiba Laptop (A Study On Students Of Economics Faculty Of Semarang University) - Prasetyo, Eko Teguh; Purwantini, Sri (Economics and Business Solutions Journal, 2017)
This study aims to analyze the influence of product quality, brand image, and price towards the decision to buy Toshiba laptop. The study is conducted on students of Economics Faculty, Semarang University. The total number of samples in the study is 96 respondents, using the purposive sampling method, while the set criteria for the said respondents are students of the Economics Faculty, Semarang University who had bought Toshiba laptop and used it for at least 3 months. Method of analysis used in this study is multiple linear regressions, the collected data which has fulfilled the validity test, reliability test, the classical assumption test, and t test that was processed using SPSS 22 program.The results of this study indicate that variables of product quality, brand image, and price positively influence significantly towards the decision to buy Toshiba laptop. Based on the above findings, it is conclusive that, altogether, the three independent variables used can influence the consumers in making their decision to buy as much as 79.5%.